(untitled) (Innovative professional education, 2025)
The implementation of a competency-based approach in the educational and production process is currently one of the main directions of modernization of the content of vocational education. The digital transformation of education emphasizes the importance of implementing the basic principles of the competency-based approach. We believe that one of the key qualities that will help future qualified workers successfully adapt to new social and production conditions is a high level of digital competence. The relevance of developing digital competence in future qualified workers is obvious, since this will allow us to effectively meet the needs of modern industry, as well as increase the competitiveness of future specialists in the labor market. Currently, the development of digital competence is a necessary element in the educational process of any vocational education institution.